2020
DOI: 10.32014/2020.2518-170x.40
|View full text |Cite
|
Sign up to set email alerts
|

The Negative Impact of Anthropogenic Factors on the State of Groundwater of Kazakhstan

Abstract: NAS RK is pleased to announce that News of NAS RK. Series of geology and technical sciences scientific journal has been accepted for indexing in the Emerging Sources Citation Index, a new edition of Web of Science. Content in this index is under consideration by Clarivate Analytics to be accepted in the Science Citation Index Expanded, the Social Sciences Citation Index, and the Arts & Humanities Citation Index. The quality and depth of content Web of Science offers to researchers, authors, publishers, and ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Also, deeper groundwater aquifers may be affected due to drawdown of the groundwater table. Previous studies in the region have shown that the drawdown of the groundwater table may be up to 80 m with a cone of depression area of up to 150 km 2 [46]. This facilitates the transport of shallow pollutants to deeper groundwater levels.…”
Section: Source Identification Of Nitratementioning
confidence: 98%
“…Also, deeper groundwater aquifers may be affected due to drawdown of the groundwater table. Previous studies in the region have shown that the drawdown of the groundwater table may be up to 80 m with a cone of depression area of up to 150 km 2 [46]. This facilitates the transport of shallow pollutants to deeper groundwater levels.…”
Section: Source Identification Of Nitratementioning
confidence: 98%
“…Currently, in Kazakhstan, Russia and several other post-Soviet countries, mainly underground mineral waters are used for balneological treatment, which in recent years have been drilled in many new areas, sometimes from very deep depths. Springs and mineral groundwater were actively studied in Soviet times, for example, hydrochemical characteristics and typification of mineral springs opened by wells in Aralsk, Chelkar, Donguztau and several other areas of Western Kazakhstan were given (Sydykov, 1999;Mukhamedzhanov et al, 2020;Osipov et al, 2020). Springs belong to the most common and numerous water bodies, collectively forming an important part of the hydrographic network of the region.…”
Section: Introductionmentioning
confidence: 99%